Herpes zoster in lupus nephritis: experience on 292 patients followed up for 15 years - Reggiani, Francesco; Cardi, Silvia; Tumminello, Fabio; Calatroni, Marta; Locatelli, Laura; Gerosa, Maria; Del Papa, Nicoletta; Moroni, Gabriella (Frontiers in Immunology, 2023)
Objectives: To evaluate the prevalence, incidence, and the predictors of herpes zoster (HZ) development in lupus nephritis (LN). Methods: This retrospective study included 292 LN patients to determine HZ incidence during the last decades and its correlation with LN activity. LN patients with HZ were matched with LN patients without HZ in a 1:2 ratio based on sex, age, year of LN diagnosis, and LN histological class at kidney biopsy, to assess HZ risk factors. Statistical tests included t-test, U test, and Fisher test. Univariate and multivariate logistic regression analyses were conducted to identify potential risk factors. Results: HZ occurred after LN diagnosis in 66 patients (prevalence 22.6%) with an average of 8.7 years (range 0.2-28.4 years) after LN diagnosis. Although with the potential limitations of the retrospective nature and the extensive duration of the study, the incidence of HZ was 15.6/1000/person-years, increasing from 6.9 before 1980 to 16.0 in the 1990s and 43.9 after 2010. HZ onset was unrelated to LN activity. LN was active in 43% of cases and quiescent in the other 57% of cases at HZ diagnosis. The percentage of patients who developed lupus flares during the year after HZ (18.9%) was not different from that which occurred during the year before HZ (17.2%, p = 0.804). After excluding confounding factors through matching, univariate analysis suggested that cyclosporin during induction therapy (p = 0.011) and higher cumulative doses of glucocorticoids (GCs > 50 grams, p = 0.004), of cyclophosphamide (CYC > 5 grams, p = 0.001), and of mycophenolate (MMF > 1000 grams, p = 0.007) predisposed patients to HZ. Univariate and multivariate analysis revealed a protective role of azathioprine (p = 0.008) and methylprednisolone pulses (p = 0.010) during induction therapy. Conclusions: HZ occurs unpredictably throughout the course of LN, underscoring the importance of continuous monitoring for these patients. In addition, the incidence of HZ seems to have increased in recent decades. Induction therapy with azathioprine and methylprednisolone pulses appears to provide protection, while higher cumulative doses of GCs, CYC, and MMF increase susceptibility.